2020
DOI: 10.1159/000510023
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of a Portuguese Single-Centre Cohort of Persons with Haemophilia and Hepatitis C Virus Infection

Abstract: Introduction: Persons with haemophilia (PWH) used to represent a population with a high prevalence of hepatitis C virus (HCV) infection due to the use of contaminated blood products. Although the goals of antiviral therapy are the same as the general population, long real-life follow-up data regarding their outcomes are still scarce. Our aim was to report the outcomes of HCV infection and the results of antiviral therapy in PWH. Methods: A retrospective analysis was performed in a single-centre cohort of PWH w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…A high rate of SVR was achieved in 73.6% of PwH treated with PegIFN+RBV in our cohort, in conjunction with an expected side-effects rate of 20.8%, which disproves healthcare providers' biases that PwH are difficult to treat with INF-based protocols. 4 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A high rate of SVR was achieved in 73.6% of PwH treated with PegIFN+RBV in our cohort, in conjunction with an expected side-effects rate of 20.8%, which disproves healthcare providers' biases that PwH are difficult to treat with INF-based protocols. 4 …”
Section: Discussionmentioning
confidence: 99%
“…The severity of hemophilia was classified as mild (5–40% of normal factor level), moderate (1–5% of normal factor level), or severe (<1% of normal factor levels). 4 According to the WFH recommendations for testing PWH for blood-borne diseases, all registered patients were tested for the presence of anti-HCV antibodies. 7 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, two treatment-naïve and 14 treatment-experienced patients were treated with DAAs, with an overall SVR-12 rate of 100%. 10 An Iranian, bicentric, retrospective study reported the treatment results of 147 patients with hereditary bleeding disorders (132 of whom suffered from haemophilia) and CHC. Six (4,1%) patients were HCV/HIV co-infected and 37 (25.2%) had cirrhosis.…”
Section: Dovepressmentioning
confidence: 99%